Selective Influence of Political Advertising on Television in Visual Image Building Candidate Presidential Election 2014 - Tuti Bahfiarti (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract: Political campaign presidential election in Indonesia has grown, along with the in creasing advances in technology and changes in the lectoral system (election). Then, the candidates vying to attract public sympathy, one way to make a Political Advertising that aired on television station. Presidential Elections (Election) in 2014 led to competition both pairs of candidates for president and vice president of the Prabowo-Hatta and Joko Widodo (Jokowi) - Jusuf Kalla (JK), heats up. The heat of competition seen also with the rise of political advertising both pairs of candidates. Political advertising is one way to get support from the community, for example in audio visual media television. The problem is how selective influence of political advertisements aired on television is able to construct a visual image of the presidential candidate in 2014. The aim was to determine the influence of selective political ad that aired in the media in the capture space “discourse” candidate image visualization massively so sehimgga able to raise the collective memory selector that will provide sound support when the momentum of the electorate was held. For the achievement of the objectives of this research are used type of research is a mixed-method research. This type of research that combines qualitative and quantitative research methods (triangulation) to provide a comprehensive analysis of the research problem. The goal is to get the data and comprehensive analysis of the research problem. The results of this study indicate that political advertisements on TV were able to build a visual image of the presidential candidates in 2014 by 87% and aims to improve the prospects of promoting the election of a candidate or candidates for president of programs and policies. Political ads this election is able to build the reputation of candidates or political parties to provide information to the public about the qualifications, experience, background, and personality presisen a candidate or political party. Then selective influence political advertising is changing, maintain adding cognitive, affective, and political behavior of audiences. The communication process takes place with all the elements involved. However, other results showed that the selective influence of political advertising in building the image visualization candidate vice effective only on the TV if it is based on specific situations, such as elections (presidential) only focused on situations in which engagement and voter interest and familiarity candidate or party chairman is quite high. The strength of political advertising in the media 2014 lies not in the idea, program, or solidity policy information directly related to the basic needs of the people. That power is the personal figure presidential candidate.Keywords: Selective Influence, Political Advertising, Television